2021
DOI: 10.1177/19714009211026924
|View full text |Cite
|
Sign up to set email alerts
|

Whole brain atlas-based diffusion kurtosis imaging parameters for evaluation of minimal hepatic encephalopathy

Abstract: Background and purposes Minimal hepatic encephalopathy (MHE) has no recognizable clinical symptoms, but patients have cognitive and psychomotor deficits. Hyperammonemia along with neuroinflammation lead to microstructural changes in cerebral parenchyma. Changes at conventional imaging are detected usually at the overt clinical stage, but microstructural alterations by advanced magnetic resonance imaging techniques can be detected at an early stage. Materials and methods Whole brain diffusion kurtosis imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…FAK is like FA to some extent measuring anisotropy but adopts the kurtosis tensor for calculation, which leads to less errors from complex white matter fiber arrangements ( 29 ). When the bulk density of fiber bundles and axons increases, it can also provide the necessary supplement for poor FA performance ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…FAK is like FA to some extent measuring anisotropy but adopts the kurtosis tensor for calculation, which leads to less errors from complex white matter fiber arrangements ( 29 ). When the bulk density of fiber bundles and axons increases, it can also provide the necessary supplement for poor FA performance ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Schindler et al showed that older rats with cognitive dysfunction after WBRT fail to show a radiation-induced decrease in neurogenesis in the hippocampus ( 38 ). DKI metrics of the clinical psychometric hepatic encephalopathy score (PHES) are correlated with the average AK and MK values in the lateral frontoorbital gyrus, caudate and thalamus rather than individual brain microstructures ( 39 ). Twelve non hippocampal regions discovered in our study, such as the left IFGoperc, right SFGmedial, right PHG, right FFG and left MTG, that are associated with cognitive changes after radiotherapy should be delineated as dose-avoidance ROIs for cognitive function protection.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between DKI and neurocognitive abnormalities may provide early and more accurate localization of brain involvement and may help in predicting prognosis and neuropsychological sequelae (6).…”
Section: Introductionmentioning
confidence: 99%